Study on association between SLC2A9 rs3733591 and Gout susceptibility in 481 Vietnamese individuals - Pham Quang Hung; Nguyen Xuan Canh; Nguyen Thuy Duong (Vietnam Journal of Science, Technology and Engineering, 2022)
Gout is a common form of inflammatory arthritis that is strongly associated with elevated uric acid concentration in the blood. The development of the disease is not only triggered by environmental factors but also genetic variations. Previous studies demonstrated that the genetic associations with gout vary in different populations in the world. This study aimed to identify the relationship between SLC2A9 rs3733591 and gout susceptibility in the Vietnamese population. Total DNAs were extracted from 481 blood samples including 160 patients with gout and 321 age-matched healthy controls. The genotyping of SLC2A9 rs3733591 was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Chi-squared test was used to test whether the genotypes frequencies of rs3733591 follow Hardy-Weinberg equilibrium (HWE) and to check its association with gout in three models (additive, recessive, dominant) and allele form. The result showed that SLC2A9 rs3733591 was in agreement with Hardy-Weinberg equilibrium (p>0.05). However, there was no association between the rs3733591 and gout in any tested models (p>0.05). This study will contribute to the genetic study of gout susceptibility in Vietnam.